A VS2 / layered silicate nanocomposite catalyst and its preparation and application

By forming a VS2/layered silicate nanocomposite catalyst on the surface of VS2 nanosheets, the problems of low exposure and poor hydrophilicity of catalytic active sites are solved, and high selectivity and cyclohexene preparation in yield.

CN116273058BActive Publication Date: 2025-02-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111520685.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-02-11
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The existing VS2 catalysts have low exposure to catalytic active sites and poor hydrophilicity in the benzene part hydrogenation and cyclohexene reaction, resulting in low selectivity and yield of cyclohexene.

Method used

By forming a VS2/layered silicate nanocomposite catalyst on the surface of the VS2 nanosheets, the hydrophilicity of the catalyst and the exposure of the catalytic hydrogenation active sites are improved.

Benefits of technology

The cyclohexene selectivity and yield of the benzene aqueous phase partial hydrogenation reaction is achieved without the need for the addition of inorganic salts, and the catalyst has high hydrophilicity and high catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003407223750000081
    Figure BDA0003407223750000081
  • Figure HDA0003407223760000011
    Figure HDA0003407223760000011
  • Figure HDA0003407223760000012
    Figure HDA0003407223760000012
Patent Text Reader

Abstract

The present invention discloses a VS2 / layered silicate nanocomposite catalyst and its preparation and application. The VS2 / layered silicate nanocomposite catalyst comprises a VS2 two-dimensional nanosheet and a single layered silicate disc, and the layered silicate disc is structurally distributed in an island-like manner on the VS2 nanosheet, and the distance between the farthest side edges of the VS2 nanosheet is much greater than the diameter of the silicate disc. The VS2 / layered silicate nanocomposite catalyst obtained by the present invention can be used for the reaction of partial hydrogenation of benzene to produce cyclohexene. The present invention solves the problems of low hydrophilicity and activity of the catalyst for partial hydrogenation of benzene in water phase, realizes high hydrophilicity and high activity exposure of the catalyst in the reaction, and finally obtains a high cyclohexene yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to a method for preparing a VS2 / layered silicate nanocomposite catalyst, belonging to a catalyst preparation technology in the technical field of industrial catalysis. Background technology:

[0002] Cyclohexene is an important organic chemical raw material. Many important fine chemicals can be produced from cyclohexene, such as polyester, food additives, medicine, pesticides and nylon. In particular, polyamide products represented by nylon-66 are widely used in automobile tires, electrical appliances, electronics and other industries. They are currently the engineering plastic products with the largest global production and market consumption. The partial hydrogenation of benzene to cyclohexene is the most important step in the new route. Although cyclohexene can also be obtained by other methods, such as cyclohexanol dehydration, cyclohexane dehydrogenation and halogenated cyclohexane dehydrohalogenation, the partial hydrogenation of benzene to cyclohexene has significant advantages such as a wide range of raw material sources, reaction atom economy and simple reaction, and has therefore been widely studied. The partial hydrogenation of benzene can be carried out in the gas phase or liquid phase. Compared with the gas phase reaction, the biggest advantage of the liquid phase reaction is that a higher cyclohexene selectivity can be obtained even when the conversion rate of benzene is high (J.Mol.Catal.A, 2003, 197, 185-191).

[0003] At present, Ru, Rh, Ni, Pt, Pd, Au and rare earth metals are mainly used in the hydrogenation of benzene to produce cyclohexene, all of which are active and selective. However, the hydrophilicity of the above catalysts in the reaction solution is poor, and inorganic salts such as zinc sulfate need to be added to the reaction system to increase the hydrophilicity of the catalyst, thereby improving the selectivity of cyclohexene. However, the zinc sulfate in the reaction solution is chemically adsorbed on the catalyst surface, thereby occupying part of the active sites. Therefore, although it can improve the selectivity of cyclohexene, it will reduce the activity of the catalyst. The development of highly active and highly hydrophilic benzene partial hydrogenation catalysts has important practical significance for improving the technical level of benzene partial hydrogenation to produce cyclohexane.

[0004] As a typical transition metal disulfide, VS2 is similar to MoS2, both of which are sandwich structures

[10] and hexagonal lamellar structures. Its solid is black powder. Transition metal V atoms are sandwiched between two layers of S atoms, forming an SVS structure through covalent bonds. The layers interact with each other by van der Waals forces, and the interlayer spacing is 0.575nm. VS2 contains two crystal structures: 1T-VS2 - the most common, with a trigonal crystal structure; 2H-VS2 - with a metallic hexagonal crystal structure

[11] . In recent years, the synthesis of VS2 has become a research hotspot. The literature (Small 2018,14,1703098) reported VS2 micron flower balls formed by nanosheet aggregation. The flower ball size is about 2μm, the VS2 nanosheet thickness is greater than 10nm, and it has abundant defect sites and enlarged interlayer spacing. CN 201710741370.4 discloses a method for preparing a graphene-modified VS2 micron flower material. The obtained graphene-modified VS2 micron flower is a micron flower self-assembled from VS2 nanosheets, and the diameter of the micron flower ball is 1.0-1.5μm. C201711377254.5 discloses a method for preparing a supercapacitor electrode material vanadium sulfide nanoflower. The vanadium sulfide nanoflower prepared by the present invention is a three-dimensional structure, which well avoids the stacking of flaky vanadium sulfide. The diameter of the nanoflower is about 3μm, and it is mainly assembled from nanosheets with a thickness of about 10-20nm. The nanosheets are wrinkled or curled to prevent aggregation or overlap. CN 201910048868.1 discloses a method for preparing a plasma-modified two-dimensional layered vanadium sulfide catalyst material. The plasma-modified two-dimensional layered vanadium sulfide catalyst materials are all spherical with a layered structure, with a diameter of 5μm, and the distribution of the layered structure on the spherical surface is more uniform, and the layer area is larger. CN 202110479841.5 discloses a method for preparing a three-dimensional rose-shaped vanadium sulfide nanosheet ball-reduced graphene oxide composite material. The diameter of a single flower ball of the VS2-reduced graphene oxide composite material is 5 μm. The rose-shaped vanadium sulfide flower ball is composed of nanosheets, wherein the thickness of a single sheet is about 200 nm.

[0005] The study found that both VS2 crystal forms have good precious metal-like properties, with an inert basal plane and no catalytic activity, and the unsaturated edge sites can be used as catalytic hydrogenation active sites (J. Mater. Chem. A., 2017, 5, 15080-15086). However, the VS2 materials prepared by the existing methods are mostly micron-sized flower ball-shaped particles, and the VS2 nanosheets thereon are several hundred nanometers in size, with a thickness greater than 10 nm, and the number of stacked layers exceeds 10 layers, and the exposure of the catalytic active sites is low. In addition, when used in the partial hydrogenation reaction of benzene, in order to obtain a high yield of cyclohexene, the hydrophilicity of the reported VS2 materials or VS2 composite materials needs to be improved. Summary of the invention:

[0006] The present invention provides a method for preparing a VS2 / layered silicate nanocomposite catalyst. The layered silicate discs composited on the surface of the composite catalyst greatly improve the hydrophilicity of the catalyst. At the same time, the nanometer size of the VS2 nanosheets greatly improves the exposure of the active sites of the catalyst, overcoming the deficiencies of the above-mentioned prior art, and can effectively solve the problems of low exposure of the catalytic active sites of the VS2 catalyst and poor hydrophilicity. The present invention improves the exposure of the VS2 catalytic hydrogenation active sites and the hydrophilicity of the VS2 / layered silicate nanocomposite catalyst by combining the layered silicate discs in an island shape on the surface of the VS2 nanosheets, thereby realizing a highly selective aqueous phase partial hydrogenation reaction of benzene without adding inorganic salts.

[0007] The present invention discloses a VS2 / layered silicate nanocomposite catalyst, in which a single-layered nano-layered silicate disk is dispersed and composited in an island shape on the surface of a VS2 nanosheet; the thickness of the VS2 nanosheet is 5 to 10 nm, and the length of the two farthest points on the side is 50 to 100 nm; the diameter of the silicate single-layered disk is 1 to 45 nm, and the thickness is 0.3 to 1.9 nm.

[0008] The present invention provides a method for preparing a VS2 / layered silicate nanocomposite catalyst, which is obtained by the following steps:

[0009] (1) dispersing at least one of natural clay and chemically synthesized layered silicate with a particle size of 10 to 100 nm in water, and forming a colorless transparent sol under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring;

[0010] (2) At least one of ammonium metavanadate, sodium orthovanadate, potassium vanadate, vanadium pentoxide, and acetylacetonato vanadyl is used as a vanadium source, and at least one of soluble sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, carbon disulfide, thioacetamide, cysteine, and glutathione is used as a sulfur source and at least one is used as a reducing agent and dissolved in ethylene glycol to form a VS2 precursor solution; the molar ratio of V / S in the precursor solution is 1:2 to 1:4, and the molar ratio of V / reducing agent is 1:1 to 1:6.

[0011] (3) The silicate sol obtained in (1) and the VS2 precursor solution obtained in (2) are mixed under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring to form a uniform mixed sol; the mass ratio of silicate to VS2 in the mixed sol is in the range of 0.1 to 10, preferably 0.5 to 2.

[0012] (4) The mixed sol obtained in (3) can be further crystallized at 140-220° C. for 3-72 hours, preferably 180-200° C. for 24-48 hours. The crystallization method can be a common crystallization method such as heating crystallization in a closed system oven, electric furnace, etc., microwave heating crystallization, open system oil bath heating crystallization, etc.; the product separation in the formed gel can be a product separation method such as polar solvent sedimentation separation, vacuum filtration separation and centrifugal separation. The product is washed with deionized water and ethanol. The product can be dried by vacuum drying, freeze drying, CO2 supercritical drying, natural air drying, etc. to obtain a VS2 / layered silicate nanocomposite catalyst.

[0013] The VS2 / layered silicate nanocomposite catalyst prepared by the present invention is used for the reaction of preparing cyclohexene by partial hydrogenation of benzene in water phase. The reaction conditions are: the mass percentage of catalyst / benzene is 0.1% to 10.0%, preferably 1.0% to 4.0%; the volume ratio of benzene to water is 1 to 5; the reaction temperature is 100 to 200° C., preferably 130 to 150° C.; the reaction pressure is 3 to 7 MPa, preferably 4 to 5 MPa.

[0014] Compared with the prior art, the present invention has the following advantages and effects:

[0015] (1) The present invention prepares a VS2 / layered silicate nanocomposite catalyst by adding a nano-layered silicate with water absorption and expansion. The nano-layered silicate microstructure is a disk with a diameter of 25nm and a thickness of 1nm. It is stacked on each other in a solid state and forms a sol after being dissolved in water under mechanical external force. The surface of a single layered silicate disk in the sol is negatively charged. After the sol is mixed with an ethylene glycol solution of a VS2 precursor, the negatively charged layered silicate disk can be adsorbed on the surface of the VS2 nanosheet to form an island-like composite, and the particle size is maintained at several tens to one hundred nanometers. Therefore, the VS2 / layered silicate nanocomposite catalyst prepared by the present invention has excellent hydrophilicity and nanometer size, which is beneficial to the partial hydrogenation of benzene in aqueous phase to produce highly selective cyclohexene.

[0016] (2) The particle size of the VS2 / layered silicate nanocomposite catalyst prepared by the present invention is about 50-100 nm (see Figure 1 ), the loose curled flake size is about 50nm, and the thickness of the flake is 7nm (see Figure 2). Due to the island-like distribution and compounding of the layered silicate disks on its surface, the growth and agglomeration of the VS2 nanosheets are suppressed, thereby obtaining a nano-sized VS2 composite catalyst. This result is completely different from the particle size of the pure VS2 catalyst of the comparative sample, which is as large as micron size, and the sheet length is greater than 200nm and the thickness is greater than 20nm. Since the catalytic hydrogenation active sites of VS2 are mainly located at the edge positions, the exposure of the active sites of the comparative VS2 sample is extremely low, and the VS2 / layered silicate nanocomposite catalyst prepared by the present invention has an extremely high exposure of the catalytic hydrogenation active sites.

[0017] (3) When the VS2 / layered silicate nanocomposite catalyst prepared by the present invention is used for the partial hydrogenation of benzene to cyclohexene in aqueous phase, there is no need to add additional inorganic salts to improve the hydrophilicity of the catalyst. The high hydrophilicity and high exposure of catalytic active sites inherent in the catalyst ensure high selectivity for cyclohexene while achieving a high conversion rate of benzene. The reaction results are shown in Table 1. The selectivity and yield of the partial hydrogenation of benzene to cyclohexene by the VS2 / layered silicate nanocomposite catalyst of the present invention can be as high as 88.0% and 47.9%, respectively, which are higher than the selectivity and yield of the partial hydrogenation of benzene to cyclohexene by the comparative sample catalyst. Description of the drawings:

[0018] Figure 1 SEM photographs of pure VS2 obtained in Comparative Example 1 and VS2 / layered silicate nanocomposite catalyst obtained in Example 1.

[0019] Figure 2 HRTEM image of the VS2 / layered silicate nanocomposite catalyst obtained in Example 1. Specific implementation method:

[0020] In order to further illustrate the present invention, embodiments are given below, but they do not limit the scope of the present invention.

[0021] Embodiment 1:

[0022] Weigh 1.0g of nano magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a single-layer disc thickness of 0.95nm measured by a nano laser particle size analyzer) and disperse it in 60ml of deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1016g of ammonium metavanadate and 0.2632g of L-cysteine ​​and dissolve them in 60ml of ethylene glycol under stirring to form a VS2 precursor solution. Under shear emulsification conditions, evenly mix the above magnesium silicate sol and VS2 precursor solution for 10 minutes to obtain a sol. The obtained sol is transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid. After freeze-drying for 12 hours, a VS2 / magnesium silicate nanocomposite catalyst is obtained.

[0023] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / magnesium silicate composite catalyst obtained in this embodiment is 93nm, so VS2 / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the VS2 / lithium-based bentonite nano-composite catalyst obtained in this embodiment is a loose flaky particle, and the length of the farthest two points on the surface of the flaky layer is about 87nm; HRTEM characterization results show that the thickness of the VS2 nanosheet is 9.0nm, and the number of stacked layers is about 14 layers; further mapping test results show that the surface of the VS2 nanosheet has an island-shaped distribution of magnesium silicate monolayer disks, with a size of about 37nm.

[0024] When the catalyst prepared in this example is used for the reaction of partial hydrogenation of benzene to cyclohexene in aqueous phase, the volume ratio of benzene to water is 2, the amount of catalyst added is 2.5wt.% of benzene, the reaction temperature is 140°C, and the hydrogen reaction pressure is 4MPa. The reaction is carried out for 4h. The reaction activity results are shown in Table 1. The activity of the VS2 / layered silicate nanocomposite catalyst for partial hydrogenation of benzene to cyclohexene is much higher than that of the comparative catalyst.

[0025] Embodiment 2:

[0026] Weigh 1.0g magnesium silicate (Shanghai Yuanye Biotechnology Co., Ltd., artificially synthesized, average particle size 73nm, single-layer disc size 32nm, single-layer disc thickness 0.95nm) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 1.0160g ammonium metavanadate and 2.6320g L-cysteine ​​and dissolve them in 60ml ethylene glycol under stirring to form a VS2 precursor solution. Mix the above magnesium silicate sol and VS2 precursor solution evenly for 10 minutes under shear emulsification conditions to obtain a sol. Transfer the obtained sol into a polytetrafluoroethylene liner and place it in a microwave synthesizer, and crystallize it in an oven at 180°C for 6 hours. After cooling to room temperature, centrifuge and wash with deionized water 3 times to obtain a black solid. After vacuum drying for 12 hours, a VS2 / magnesium silicate nanocomposite catalyst is obtained.

[0027] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / magnesium silicate composite catalyst obtained in this embodiment is 85nm, so VS2 / magnesium silicate is a nano-composite catalyst. SEM characterization shows that the VS2 / lithium-based bentonite nano-composite catalyst obtained in this embodiment is a loose, curled flaky particle, and the length of the farthest two points on the surface of the flaky layer is about 83nm; HRTEM characterization results show that the thickness of the VS2 nanosheet is 9.8nm, and the number of stacked layers is about 16; further mapping test results show that the surface of the VS2 nanosheet has island-shaped lithium-based bentonite monolayer discs with a size of about 30nm.

[0028] When the catalyst prepared in this example is used for the partial liquid phase hydrogenation of benzene to cyclohexene, the volume ratio of benzene to water is 3, the amount of catalyst added is 2.5wt.%, the reaction temperature is 150°C, and the hydrogen reaction pressure is 5MPa for 4h. The reaction activity results are shown in Table 1. The activity of the VS2 / layered silicate nanocomposite catalyst for partial hydrogenation of benzene to cyclohexene is much higher than that of the comparative catalyst.

[0029] Embodiment 3:

[0030] Weigh 1.0g of Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single-layer disc size 25nm, single-layer disc thickness 0.92nm) and disperse it in 60ml of deionized water, and mechanically stir for 1 hour to form a colorless and transparent sol. Weigh 1.5982g of sodium orthovanadate, 1.3584g of thioacetamide, and 1.2984g of hydroxylamine hydrochloride and dissolve them in 60ml of ethylene glycol under stirring to form a VS2 precursor solution. Under shear emulsification conditions, the above Laponite sol and VS2 precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized at 180°C for 12 hours. After cooling to room temperature, it is filtered after sedimentation, washed with deionized water 3 times, and washed with ethanol 3 times to obtain a black solid, which is naturally dried for 24 hours to obtain a VS2 / Laponite nanocomposite catalyst.

[0031] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / Laponite composite catalyst obtained in this embodiment is 58nm, so VS2 / Laponite is a nano-composite catalyst. SEM characterization shows that the VS2 / lithium-based bentonite nano-composite catalyst obtained in this embodiment is a loose curled flaky particle, and the length of the farthest two points on the surface of the flaky layer is about 64nm; HRTEM characterization results show that the thickness of the VS2 nanosheet is 8nm, and the number of stacked layers is about 14; further mapping test results show that the surface of the VS2 nanosheet has island-shaped lithium-based bentonite monolayer discs with a size of about 25nm.

[0032] When the catalyst prepared in this example is used for the reaction of partial hydrogenation of benzene to cyclohexene in aqueous phase, the volume ratio of benzene to water is 4, the amount of catalyst added is 2.5wt.%, the reaction temperature is 100°C, and the hydrogen reaction pressure is 7MPa. The reaction is carried out for 4h. The reaction activity results are shown in Table 1. The activity of the VS2 / layered silicate nanocomposite catalyst for partial hydrogenation of benzene to cyclohexene is much higher than that of the comparative catalyst.

[0033] Embodiment 4:

[0034] Weigh 0.5g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, single layer disc thickness 0.92nm) and disperse it in 60ml deionized water, and stir magnetically for 1 hour to form a colorless and transparent sol. Weigh 1.5982g sodium orthovanadate, 1.4122g thiourea, and 4ml hydrazine hydrate and dissolve them in 60ml ethylene glycol under stirring to form a VS2 precursor solution. Under magnetic stirring conditions, the above Laponite sol and VS2 precursor solution are uniformly mixed for 1 hour to obtain a sol. The obtained sol is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid, which is vacuum dried for 24 hours to obtain a VS2 / Laponite nanocomposite catalyst.

[0035] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / Laponite composite catalyst obtained in this embodiment is 50nm, so VS2 / Laponite is a nano-composite catalyst. SEM characterization shows that the VS2 / lithium-based bentonite nano-composite catalyst obtained in this embodiment is a loose curled sheet-like particle, and the length of the farthest two points on the sheet surface is about 55nm; HRTEM characterization results show that the thickness of the VS2 nanosheet is 5.5nm, and the number of stacked layers is about 8 layers; further mapping test results show that the surface of the VS2 nanosheet has island-shaped lithium-based bentonite monolayer discs with a size of about 23nm.

[0036] When the catalyst prepared in this example is used for the reaction of partial hydrogenation of benzene to cyclohexene in aqueous phase, the volume ratio of benzene to water is 1, the amount of catalyst added is 2.5wt.%, the reaction temperature is 200°C, and the hydrogen reaction pressure is 3MPa for 4h. The reaction activity results are shown in Table 1. The activity of the VS2 / layered silicate nanocomposite catalyst for partial hydrogenation of benzene to cyclohexene is much higher than that of the comparative catalyst.

[0037] Embodiment 5:

[0038] Weigh 0.1g of lithium magnesium silicate (synthesized by hydrothermal method, the average particle size is 45nm, the single-layer disc size is 20nm, and the single-layer disc thickness is 1.0nm) and disperse it in 60ml of deionized water. Stir magnetically for 1 hour to form a colorless and transparent sol. Weigh 2.1140g of potassium vanadate, 2.0346g of sodium sulfide, and 4ml of hydrazine hydrate and dissolve them in 60ml of ethylene glycol under stirring to form a VS2 precursor solution. Under magnetic stirring conditions, the above-mentioned lithium magnesium silicate sol and VS2 precursor solution are uniformly mixed for 1 hour to obtain a sol. The obtained sol is transferred to a hydrothermal kettle with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, it is directly filtered and washed with deionized water 3 times to obtain a black solid. After vacuum drying for 24 hours, a VS2 / lithium magnesium silicate nanocomposite catalyst is obtained.

[0039] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / lithium magnesium silicate composite catalyst obtained in this embodiment is 68nm, so VS2 / lithium magnesium silicate is a nano-composite catalyst. SEM characterization shows that the VS2 / lithium-based bentonite nano-composite catalyst obtained in this embodiment is a loose curled flaky particle, and the length of the farthest two points on the surface of the flaky layer is about 62nm; HRTEM characterization results show that the thickness of the VS2 nanosheet is 6nm, and the number of stacked layers is about 10; further mapping test results show that the surface of the VS2 nanosheet has island-shaped lithium-based bentonite monolayer discs with a size of about 18nm.

[0040] When the catalyst prepared in this example is used for the reaction of partial hydrogenation of benzene to cyclohexene in aqueous phase, the volume ratio of benzene to water is 5, the amount of catalyst added is 2.5wt.%, the reaction temperature is 130°C, and the hydrogen reaction pressure is 6MPa, and the reaction is carried out for 4h. The reaction activity results are shown in Table 1. The activity of the VS2 / layered silicate nanocomposite catalyst of the present invention for partial hydrogenation of benzene to cyclohexene is much higher than that of the comparative catalyst.

[0041] Embodiment 6:

[0042] Weigh 0.5g lithium bentonite (Shanghai Aladdin Biochemical Technology Co., Ltd., natural clay, average particle size 90nm, single layer disc size 40nm, single layer disc thickness 1.0nm) and disperse it in 60ml deionized water, 13000r.mp shear emulsification for 10 minutes to form a colorless and transparent sol. Weigh 2.1140g potassium vanadate, 2.0346g sodium sulfide, and 4ml hydrazine hydrate and dissolve them in 60ml ethylene glycol under stirring to form a VS2 precursor solution. Under shear emulsification conditions, the above lithium bentonite sol and VS2 precursor solution are uniformly mixed for 10 minutes to obtain a sol. The obtained sol is transferred to a round-bottom flask with a reflux device and crystallized at 120°C in an oil bath for 60 hours. After cooling to room temperature, it is filtered after sedimentation, washed with deionized water 3 times to obtain a black solid, and freeze-dried for 6 hours to obtain a VS2 / lithium bentonite nanocomposite catalyst.

[0043] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / lithium-based bentonite composite catalyst obtained in this embodiment is 95nm, so the VS2 / lithium-based bentonite is a nano-composite catalyst. SEM characterization shows that the VS2 / lithium-based bentonite nano-composite catalyst obtained in this embodiment is a loose, curled flaky particle, and the length of the farthest two points on the surface of the flaky layer is about 80nm; HRTEM characterization results show that the thickness of the VS2 nanosheet is 7nm, and the number of stacked layers is about 12; further mapping test results show that the surface of the VS2 nanosheet has island-shaped lithium-based bentonite monolayer discs with a size of about 41nm.

[0044] When the catalyst prepared in this example is used for the reaction of partial hydrogenation of benzene to cyclohexene in aqueous phase, the volume ratio of benzene to water is 3, the amount of catalyst added is 2.5wt.%, the reaction temperature is 180°C, and the hydrogen reaction pressure is 3MPa, and the reaction is carried out for 4h. The reaction activity results are shown in Table 1. The activity of the VS2 / layered silicate nanocomposite catalyst for partial hydrogenation of benzene to cyclohexene is much higher than that of the comparative catalyst.

[0045] Comparative Example 1:

[0046] Weigh 0.0508g of ammonium metavanadate and 0.1316g of L-cysteine ​​and dissolve them in 60ml of water under stirring to form a VS2 precursor solution. The resulting sol was transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C for 24 hours. After cooling to room temperature, it was separated by suction filtration and washed with deionized water three times to obtain a black solid. After freeze drying for 12 hours, a pure VS2 catalyst was obtained.

[0047] SEM characterization shows that the average particle size of the pure VS2 catalyst obtained in this comparative example is 1 μm, which is a solid aggregate of VS2 nanosheets. The length of the two farthest points of the sheet is greater than 200 nm, and the sheet thickness is greater than 20 nm. HRTEM characterization results show that the number of stacked layers of VS2 nanosheets is greater than 30, and the amount of exposed catalytic hydrogenation active sites is small.

[0048] Comparative Example 2:

[0049] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a single-layer disc thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1022g ammonium tungstate and 0.2438g cysteine ​​and dissolve them in 60ml water under stirring. Add 5ml ammonia water to adjust the pH until all dissolved to form a red WS2 precursor solution. Under shear emulsification conditions, the above magnesium silicate sol and WS2 precursor solution are uniformly mixed for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid. After freeze-drying for 12 hours, a WS2 / magnesium silicate nanocomposite catalyst is obtained.

[0050] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / magnesium silicate composite catalyst obtained in this embodiment is 35nm, so WS2 / magnesium silicate is a nano-composite catalyst. HRTEM characterization results show that the nanosheet can be composited on the upper and lower surfaces of a single magnesium silicate disk, thus forming a parallel sandwich composite structure; the thickness of a single WS2 nanosheet is about 4nm, and the length of the farthest two points on the side of the sheet is 35nm.

[0051] Comparative Example 3:

[0052] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a single-layer disc thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1104g ammonium heptamolybdate and 0.2556g cysteine ​​and dissolve them in 60ml water under stirring to form a red MoS2 precursor solution. Under 13000r.mp shear emulsification conditions, evenly mix the above-mentioned magnesium silicate sol and MoS2 precursor solution for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized at 160°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid, which is freeze-dried for 12 hours to obtain a MoS2 / magnesium silicate composite catalyst.

[0053] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / magnesium silicate composite catalyst obtained in this embodiment is 83nm, so MoS2 / magnesium silicate is a nano-composite catalyst. The SEM characterization results of the MoS2 / magnesium silicate nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet of island-like composite on the surface of a single layered magnesium silicate lithium disk with a size of 40nm. The HRTEM characterization results show that the number of stacked layers of a single MoS2 nano-sheet is 2, the thickness of the sheet is about 1.5nm, and the length of the two farthest points on the side of the sheet is 6-8nm.

[0054] When the catalyst prepared in Comparative Examples 1-3 was used for the partial hydrogenation of benzene in aqueous phase to produce cyclohexene, the volume ratio of benzene to water was 2, the amount of catalyst added was 2.5wt.%, the reaction temperature was 140°C, and the hydrogen reaction pressure was 4MPa for 4h. The reaction activity results are shown in Table 1.

[0055] Table 1 Partial liquid phase hydrogenation activity of benzene of the VS2 / layered silicate nanocomposite catalyst prepared by the present invention and the control sample catalyst.

[0056]

Claims

1. A VS2 / layered silicate nanocomposite catalyst, characterized in that: The nanocomposite catalyst comprises VS2 nanosheets and single layered silicate disks, and is a VS2 / layered silicate nanocomposite catalyst formed by island-like dispersion and compounding of single-layered nanolayered silicate disks on the surface of VS2 nanosheets. The thickness of the VS2 nanosheet is 5-10 nm, and the distance between the two farthest points on the side edge of the nanosheet surface is 50-100 nm. The preparation of VS2 / layered silicate nanocomposite catalyst comprises the following steps: (1) Dispersing layered silicate in water to form a colorless and transparent sol under the action of mechanical external force; (2) dissolving one or a mixture of two or more of ammonium metavanadate, sodium orthovanadate, potassium vanadate, vanadium pentoxide, and acetylacetonato vanadyl as a vanadium source and a sulfur source in ethylene glycol to form a VS2 precursor solution; (3) mixing the colorless transparent sol obtained in step (1) and the VS2 precursor solution obtained in step (2) under the action of an external mechanical force to form a uniform mixed sol; (4) subjecting the mixed sol obtained in step (3) to heat treatment and crystallization, cooling the mixed sol, separating the product in the formed gel, and fully drying the mixed sol to obtain a VS2 / layered silicate nanocomposite catalyst; The crystallization temperature of the mixed sol in step (4) is 120 to 220° C., and the crystallization time is 3 to 72 hours; The layered silicate used is a mixture of one or more of natural clay with a particle size of 10 to 100 nm and chemically synthesized layered silicates, wherein the chemically synthesized layered silicate is one or more of magnesium silicate, lithium magnesium silicate, and sodium magnesium lithium silicate. The sulfur source used is one or a mixture of two or more of soluble sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, carbon disulfide, thioacetamide, cysteine, and glutathione; The mass ratio of layered silicate to VS2 in the composite catalyst is 0.1-10.

2. The VS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The single-layer nano-layered silicate disk has a diameter of 1-45 nm and a thickness of 0.3-1.9 nm.

3. The VS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The molar ratio of V / S in step (2) is 1:2-1:4; the mass ratio of layered silicate to VS2 in the mixed sol in step (3) is 0.1-10.

4. The VS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The mass concentration of the layered silicate in the mixed sol in step (3) is in the range of 0.8 to 35 mg / ml.

5. The VS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The mass ratio of layered silicate to VS2 in the mixed sol in step (3) is 0.5-2; the crystallization temperature of the mixed sol in step (4) is 140-180° C., and the crystallization time is 24-48 hours.

6. The VS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The mechanical external force used to form the sol is one or more of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring.

7. Use of the VS2 / layered silicate nanocomposite catalyst according to any one of claims 1 to 6 in the reaction of preparing cyclohexene by partial hydrogenation of benzene in aqueous phase.

8. The use of the VS2 / layered silicate nanocomposite catalyst according to claim 7 in the reaction of preparing cyclohexene by partial hydrogenation of benzene in aqueous phase, characterized in that: The conditions for the aqueous phase hydrogenation reaction are: the mass percentage of catalyst / benzene is 0.1% to 10.0%, the volume ratio of benzene to water is 1 to 5; the reaction temperature is 100 to 200° C.; and the hydrogen reaction pressure is 3 to 7 MPa.

9. The use of the VS2 / layered silicate nanocomposite catalyst according to claim 8 in the reaction of preparing cyclohexene by partial hydrogenation of benzene in aqueous phase, characterized in that: The mass percentage of catalyst / benzene is 1.0%~4.0%; the volume ratio of benzene / water is 1~5; the reaction temperature is 130~150℃; and the hydrogen reaction pressure is 4~5MPa.

Citation Information

Patent Citations

  • Graphene-modified vanadium disulfide micrometer flower material, preparation method thereof and application of graphene-modified vanadium disulfide micrometer flower material as aluminum ion battery cathode material

    CN107482161A

  • A method for preparing plasma-modified two-dimensional layered vanadium sulfide catalyst material

    CN109701558B

  • Preparation and application of a three-dimensional rose-shaped vanadium sulfide nanosheet sphere-reduced graphene oxide composite material

    CN113247949B

  • Method for preparing cyclohexene catalyst through partial hydrogenation of benzene, and method for producing cyclohexene through using cyclohexene catalyst

    CN103191732A

  • Preparation method for nano-scale supported molybdenum sulphide catalyst

    CN109465018A